2013
DOI: 10.1016/j.nano.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle translocation across mouse alveolar epithelial cell monolayers: Species-specific mechanisms

Abstract: Studies of polystyrene nanoparticle (PNP) trafficking across mouse alveolar epithelial cell monolayers (MAECM) show apical-to-basolateral flux of 20 and 120 nm amidine-modified PNP is ~65 times faster than that of 20 and 100 nm carboxylate-modified PNP, respectively. Calcium chelation with EGTA has little effect on amidine-modified PNP flux but increases carboxylate-modified PNP flux ~50-fold. PNP flux is unaffected by methyl-β-cyclodextrin while ~70% decrease in amidine- (but not carboxylate-) modified PNP fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
2
11
0
1
Order By: Relevance
“…Consistent with this hypothesis, human studies which exposed healthy and COPD patients to inhaled nanoparticles showed that the deposition of particles increases with the severity of the disease [18], suggesting that penetration or translocation of these minute particles through the respiratory epithelium into the lung parenchyma increases when the alveolar barrier is inflamed. Consistent with those results, in vitro studies showed that a pharmacological decrease in the tight junctional resistance of mouse alveolar epithelial cell monolayers causes a drastic increase in the translocation of engineered nanoparticles across the epithelial barrier [19] and that smaller nanoparticles cross the rat alveolar epithelial monolayer 3 times faster than larger ones [20], observations which can explain the shift towards larger particles in our inflammatory models. If so, our results also predict that any inflammatory imbalance of the lung epithelial layer, regardless of its cause and magnitude, results in a similar absorption of small UFP in the lung.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with this hypothesis, human studies which exposed healthy and COPD patients to inhaled nanoparticles showed that the deposition of particles increases with the severity of the disease [18], suggesting that penetration or translocation of these minute particles through the respiratory epithelium into the lung parenchyma increases when the alveolar barrier is inflamed. Consistent with those results, in vitro studies showed that a pharmacological decrease in the tight junctional resistance of mouse alveolar epithelial cell monolayers causes a drastic increase in the translocation of engineered nanoparticles across the epithelial barrier [19] and that smaller nanoparticles cross the rat alveolar epithelial monolayer 3 times faster than larger ones [20], observations which can explain the shift towards larger particles in our inflammatory models. If so, our results also predict that any inflammatory imbalance of the lung epithelial layer, regardless of its cause and magnitude, results in a similar absorption of small UFP in the lung.…”
Section: Discussionsupporting
confidence: 82%
“…Agglomerates of ENM form in biological fluids by loose binding (e.g., van der Waals force) while primary diameters, and not hydrodynamic diameters influence toxicity. In support of this, other researchers have reported that nanoparticle trafficking across lung epithelial cells was correlated with primary diameters and not the hydrodynamic diameters of the agglomerated nanoparticles [ 22 ].…”
Section: Discussionmentioning
confidence: 71%
“…Besides secretion of surfactant, ATII cells have also been shown to sense invading pathogens to produce antimicrobial products and amplify the inflammatory response by secretion of cytokine and chemokines [61,62]. Particularly for nanoparticles, the alveolar epithelial layer has been described to accomplish uptake and translocation of deposited materials [63,64]. For agglomerated carbonaceous particles this process might however be not effective enough [65] to a detection of epithelial internalized CNP agglomerates by light microscopy (Fig.…”
Section: Discussionmentioning
confidence: 99%